Storm‑Time Variability of GNSS‑Derived Ionospheric VTEC over East Africa during Four Major Geomagnetic Storms of Solar Cycle 24 - Muniafu, Wilberforce; Uluma, Edward; Lomotey, Solomon Otoo; Tilahun, Atirsaw Muluye; Mefe, Moses; Muriithi, Joseph Kagotho; Omondi, George; Ndinya, Boniface (Earth and Planetary Science, 2026)
This study investigates the ionospheric response to four major geomagnetic storms during solar cycle 24 (18–19 February, 2014, Dst minimum −119 nT; 17–18 March, 2015, Dst minimum −223 nT; 22–23 June, 2015, Dst minimum −204 nT; and 8 September, 2017, Dst minimum −142 nT) using Vertical Total Electron Content (VTEC) data derived from Global Navigation Satellite System (GNSS) observations over the East African region. Our results revealed substantial storm-time VTEC variability characterized by both positive and negative ionospheric phases. The main phases of the storms had significant VTEC enhancements, especially near the Equatorial Ionization Anomaly (EIA) crest. This was attributed to the intensified equatorial fountain process which was primarily driven by Prompt Penetration Electric Fields (PPEF). In contrast, reductions in VTEC were observed during quiet periods. This was attributed to the effect of Disturbance Dynamo Electric Fields (DDEF), compositional changes in the upper atmosphere and storm-induced thermospheric winds. Clear spatial differences in VTEC responses across the GNSS stations were noted, indicating a strong influence of the equatorial electrodynamics on ionospheric variability. The results underscore the critical role of GNSS observations in monitoring space weather impacts and enhancing the understanding of storm-time ionospheric dynamics over the equatorial East African region, which has historically remained underexplored. ER